Mastering complexity: towards bottom-up construction of multifunctional eukaryotic synthetic cells - Göpfrich, Kerstin; Platzman, Ilia; Spatz, Joachim P. (Trends in biotechnology, 2018)
With the ultimate aim to construct a living cell, bottom-up synthetic biology strives to reconstitute cellular phenomena in vitro - disentangled from the complex environment of a cell. Recent work towards this ambitious goal has provided new insights into the mechanisms governing life. With the fast-growing library of functional modules for synthetic cells, their classification and integration become increasingly important. We discuss strategies to reverse-engineer and recombine functional parts for synthetic eukaryotes, mimicking the characteristics of nature’s own prototype. Particularly, we focus on large outer compartments, complex endomembrane systems with organelles, and versatile cytoskeletons as hallmarks of eukaryotic life. Moreover, we identify microfluidics and DNA nanotechnology as two technologies that can integrate these functional modules into sophisticated multifunctional synthetic cells.
Gesehen am 08.05.2019